2015
DOI: 10.1166/jnn.2015.9544
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Magnetic Properties of Iron Oxide Nanoparticles by a Room-Temperature Air-Atmosphere (RTAA) Co-Precipitation Method

Abstract: The ability of a room-temperature air-atmosphere (RTAA) co-precipitation method to tune the magnetic properties of iron oxide nanoparticles was investigated. It was demonstrated that superparamagnetic nanoparticles with different particle sizes ranging from 7 to 25 nm and magnetic properties with saturation magnetization between 2 to 75 emu g(-1) can be synthesized by simply controlling the molar ratio of ferrous to ferric ions and the concentration of ammonium solution, without heat treatment or oxygen-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…In the previous studies, it was stated that when Fe 2+ /Fe 3+ ions with a 3/1 ratio was used in the synthesis under air atmosphere, higher saturation magnetization (Ms) values were obtained for spherical Fe3O4 nanoparticles [23]. Different to such reports, we found that the presence of iron oxide nanoflakes were observed for the same Fe 2+ /Fe 3+ ratio in air atmosphere, as seen in Fig.…”
Section: Morphology and Size Analysis Of Spionscontrasting
confidence: 82%
See 1 more Smart Citation
“…In the previous studies, it was stated that when Fe 2+ /Fe 3+ ions with a 3/1 ratio was used in the synthesis under air atmosphere, higher saturation magnetization (Ms) values were obtained for spherical Fe3O4 nanoparticles [23]. Different to such reports, we found that the presence of iron oxide nanoflakes were observed for the same Fe 2+ /Fe 3+ ratio in air atmosphere, as seen in Fig.…”
Section: Morphology and Size Analysis Of Spionscontrasting
confidence: 82%
“…It has been previously shown by Vikram et al that saturation magnetization and particle size can be changed by varying the molar ratio of Fe 2+ to Fe 3+ ions and concentration of base in air atmosphere [23]. It has also been shown that smaller particle size and improved magnetic properties could be obtained by changing the base used [24].…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic response of iron oxide is related to nanoparticle size; specifically the critical diameter for single domain particle formation ( D sd ) of Fe 3 O 4 is ~80 nm at room temperature 58 . Whereas, particles of smaller size (25–30 nm) approach the lower critical diameter for superparamagnetic response ( D sp ) characterized by a fast flipping of the magnetization vectors presenting vanishing magnetization values 58 59 . Micromagnetic simulations of the equilibrium magnetization of Fe 3 O 4 particles were computed to analyze the direct visualizations by holography.…”
Section: Discussionmentioning
confidence: 99%
“…The surfactant used was fine white Lithium grease, the grease was thoroughly mixed with carrier oil for around 2 h and then the carbonyl-iron particles were added to the mixture and were well stirred for another one h. Hence, we could obtain a homogenous mixture of MR fluid. Preparation of magneto-rheological fluid is explained in article (Vikram, 2014). It was decided to arrive at a set of MR fluid damper parameters namely the shape of the plunger (S), the viscosity index of the fluid medium (p) , size of the ferro magnetic particle (m) and the current through the coil(I) to minimize tool vibration.…”
Section: Preparation Of Mr Fluid Samples and Experimentationmentioning
confidence: 99%